Analysis of the electromagnetic compatibility of the frequency band 790-862 MHz in the territory of Ukraine for the introduction of a mobile communication network using LTE technology - Lebedev, V.O.; Makarov, S.А.; Vysotskyy, O.V. (Radiotekhnika, 2017)
The transition to new technologies and standards requires a study of the specifics of the electro-magnetic interacting bonds between the radioelectronic facilities of special and general users. An important further development reserve of radio spectrum for the development of new technology is the conversion and the release of the spectrum allocated for the use of special tools and commercial applications in the range 790 – 862 MHz.